ANALYSIS OF THE APPLICATION OF ANDROID-BASED ACCOUNTING APPLICATIONS TO COMPILE FINANCIAL REPORTS AT THE WORKSHOP PERKASA AUTORESTO AND CLUB TEGAL - Hilda Paramadina Puspaningrum Haliem; Yeni Priatna Sari; Aryanto Aryanto (Politeknik Negeri Semarang, 2023)
Bengkel Perkasa Autoresto and Club Tegal are MSMEs engaged in services that have not made financial reports in accordance with applicable standards. This study aims to helps Bengkel Perkasa Autoresto and Club in arrange and produce financial reports by implement an android-based accounting application, named SI APIK. The results of these financial statements can be used by the company to know the profite and loss obtained. This type of research is qualitative research use descriptive method. The data collection technique used in this research is by conduct interview, observation, documentation, and literature study. Based on the research results, the application of SI APIK can be used easily. SI APIK application helps Bengkel Perkasa in arrange financial reports according to SAK EMKM so that it can find out profit or loss obtained.